Respon Jagung Manis (Zea mays, Sacharata SHOUT) Terhadap Penggunaan Mulsa dan Pupuk Organik - Erita Hayati; A. Halim Ahmad; Cut Taisir Rahman (Fakultas Pertanian, Universitas Syiah Kuala, 2010)
The Response of Sweet Corn (Zea mays, Sacharate SHOUT) on Mulch and Organic FertilizerABSTRACT. This study aims to determine the response of maize (Zea mays, Sacharata SHOUT) against the use of several types of organic mulch and organic fertilizer super nasa and whether there is an interaction between both factors. This research has been conducted in the village of Kuala Batee, Terbue District of Southwest Aceh district which lasted from 17 july - 30 october 2008, and with Research Randomized factorial arranged with the combined treatment of organic mulch (M) that M1 = straw, M2 = bagase, M3= rice husk, while the organic fertilizer treatments super nasa (P) is P1 = 10 g / l of water, P2 = 20 g / l of water and P3 = 30 g / l of water with three replications. Results showed that oral administration of organic mulch significantly affect corn production, the best production of mulch was found in rice husk (M3) significant than other types of organic mulch. Fertilizer did not affect the process of growth and yield of maize. There is interaction between the type of Mulching with organic fertilizer super nasa. The best combination was obtained in the combined treatment M2P1 or M3P3.